Knowledge and perception of Malaysian forest fringe population towards Zika infection - Rozita Hod,; Wong, Chin Mun; Mohd Rohaizat Hassan,; Nadia Aqilla Shamsusah,; Hani Kartini A,; Raja Mohd Azim RH,; Sharifa Ezat Wan Puteh,; Sazaly AB, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
The World Health Organization (WHO) has declared Zika infection as Public Health Emergency of International Concern in 2016. In this study, we aimed to assess the knowledge and risk perception towards Zika infection among the forest fringe population in Malaysia. A cross-sectional study of with 433 adult respondents in Malaysia completed the assisted-administered validated questionnaire on knowledge and perception to Zika infection. Bidirectional analysis on the person and item abilities were tested using Statistical Package for the Social Sciences (SPSS) and Rasch. The knowledge and perception levels were tested against significant sociodemographic or socioeconomic variables using Pearson’s Chi Square; covariates were then adjusted at multivariate level using binary logistic regression. Both knowledge and perception domains were well-targeted. Complementing results from SPSS and Rasch showed poor knowledge and poor risk perception levels in slightly more than half of the respondents [knowledge score: 50.8% (SPSS), 55.4% (Rasch); perception score: (58.0% (SPSS), 58.2% (Rasch)]. With covariates adjusted, non-bumiputra (non-natives) of higher education level, higher household income and recent jungle visits showed good knowledge level. Adult, menopaused women from Perak state showed better risk perception level towards Zika. Majority of the forest fringe population in Malaysia have poor knowledge and risk perception towards the Zika infection. This questionnaire is a suitable tool to assess knowledge and perception towards Zika infection among the forest fringe populations in Southeast Asia.